Analisis Pemasaran TikTok Shop terhadap Penjualan Usaha Mikro, Kecil, Menengah (UMKM) dalam Akad Salam - Muhamamd Farhan Suhendi; Moh. Mukhisn (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the influence of live shopping features, seller interactions on social media, and flash sale strategies on the improvement of online Micro, Small, and Medium Enterprises product sales through TikTok Shop, examined from a sharia perspective using the salam contract. The research is motivated by the rapid growth of e-commerce, which provides significant opportunities for Micro, Small, and Medium Enterprises, while raising questions regarding its compliance with Islamic commercial principles. This study employs a quantitative approach, with independent variables consisting of live shopping, seller interaction, and flash sale, and the dependent variable being the improvement of online Micro, Small, and Medium Enterprises product sales. The findings are expected to contribute theoretically to Islamic economic literature, particularly regarding the implementation of salam contracts in the digital era, as well as to provide practical benefits for Micro, Small, and Medium Enterprises, consumers, academics, and regulators in developing marketing strategies and policies aligned with sharia principles.